AC electrophoretic deposition of organic-inorganic composite coatings - Yoshioka, T.; Chavez-Valdez, Alejandra; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of Colloid and Interface Science, 2013)
Alternating current electrophoretic deposition (AC-EPD) of polyacrylic acid (PAA)-titanium oxide (TiO2) nanoparticle composites on stainless steel electrodes was investigated in basic aqueous solution. AC square wave with duty cycle of 80% was applied at a frequency of 1kHz. FTIR-ATR spectra showed that both AC and direct current (DC) EPD successfully deposited PAA-TiO2 composites. The deposition rate using AC-EPD was lower than that obtained in direct current DC-EPD. However, the microstructure and surface morphology of the deposited composite coatings were different depending on the type of electric field applied. AC-EPD applied for not more than 5min led to smooth films without bubble formation, while DC-EPD for 1min or more showed deposits with microstructural defects possibly as result of water electrolysis. AC-EPD was thus for the first time demonstrated to be a suitable technique to deposit organic-inorganic composite coatings from aqueous suspensions, showing that applying a square wave and frequency of 1kHz leads to uniform PAA-TiO2 composite coatings on conductive materials. © 2012 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.acelec
Keywords: Alternating current (AC); Coatings; Composites; Electrophoretic deposition (EPD); Nanoparticles; Polyacrylic acid (PAA); Titanium oxide (TiO